Parental Skills and Academic Competences in School Children: The Mediator Role of Executive Functions - Azar Zimmermann, Elisa Emma (2023)
The role of parenting in the development of children’s learning constitutes, at present, part of the discussion in the psychoeducational field. Although parental competences (pc) and executive functions (ef) have been investigated by psychology and neuropsychology, their relationship with academic competences remains to be fully studied. The aim of this investigation was to analyze the effect of pc perceived by parents on behavioral ef and performance-based measures of reading and mathematical competences in children. We worked with 131 school children of both sexes, between 9 and 11 years old, and their respective parents. Multivariate Analysis of Variance (manova) and structural equation model (sem) were used. The results indicate that parental skills from the parents’ perspective have a significant effect on ef, reading, and mathematical skills. However, the best fit model indicates that efs mediate the relationship between parenting skills and reading and math skills.